A study of contextual vowel nasalization in standard peninsular Spanish - Fernández Planas, Ana Ma. (Onomázein, 2020)
Since Navarro Tomás (1918) it is well known in Spanish phonetics that vowels between nasals become nasalized and that vowels followed by a nasal in syllable coda position might undergo a certain degree of nasalization, even if Spanish does not have nasal vowels from the phonological point of view. This study aims to explore this phenomenon through the use of a Nasometer by examining several nasal-vowel contexts (NV, VN, and NVN sequences, and with post-vocalic nasals in tautosyllabic or heterosyllabic sequences with reference to the preceding vowel), the distinction between stressed and unstressed syllables containing the target vowel, and three speaking rate conditions (slow, normal, and fast). The utterances produced by three speakers of standard peninsular Spanish are analyzed. Results of the percentage of nasality and nasalance indicate that the variables under examination are statistically significant in the process of vowel nasalization, though to a varying extent. A closer look at the different syllable positions in the nasal-vowel relationship addresses the issue of anticipatory vs. carryover coarticulation effects on vowel nasalization.